How Non-Muslim Communities Interact With Muslim Domination In Sungai Penuh City? - Juwita, Utari Maysa; Wulandari, Febri (Institut Agama Islam Negeri Kerinci, 2022)
Social interaction between Muslims and non-Muslims and vice versa does not always go smoothly and harmoniously. Religious conflicts continue to occur that are contrary to the values and principles of religious teachings. This article studies the harmony of non-Muslim life alongside Islamic rules in Sungai Penuh City, Jambi Province. This article aims to understand the social interaction pattern between Muslim and non-Muslim communities in Sungai Penuh City, Jambi Province. This study used a qualitative descriptive approach, and data was collected through observation, interviews, documentation, and analysis from several other supporting journals. The study results show that social interaction between Muslims and non-Muslims is manifested in an attitude of mutual respect and respect for each other's beliefs and culture so that they can live together amid the struggle of multi-religious life. Social interaction of the community in religious harmony is a form of socialization that creates tolerance, namely mutual understanding, respect, and respect without discrimination, especially in religious matters.